IMPROVING BUSINESS INDEPENDENCE OF COLLEGE STUDENTS’ GENERATION-Z THROUGH BEHAVIOR ENTREPRENEURSHIP DURING PANDEMIC COVID-19 - Meilani, Yohana F. Cahya Palupi (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2022)
In this study, the purpose of this research is to examine the relationship between entrepreneurial spirit and entrepreneurial value to increase business independence through entrepreneurial behavior in generation Z. Entrepreneurship in generation Z still need to be increased. In this study using quantitative methods, namely the data collection using a questionnaire that is taken directly. This study uses a non-probability sampling method, as convenience sampling for college students that their Universities has incubator business in Jakarta and Tangerang. The data collection of generation Z  college students who have businesses over 1 year. The sample in this study was 108 respondents. Analysis data used Partial Least Square and  data processing used applications, SmartPLS 3.2.4 Software. The result shown all hypotheses are supported. Contribution of this study can be used in related education in Universities to understand the way to increase business independence of generation Z through entrepreneurial behavior.